An investigation into the challenges faced by nomadic learners of Namibia in meeting their educational provision. - Kauuola, Tjipikita (Midlands State University, 2017)
The study explored into the challenges encountered by the nomadic learners (Himba and Zemba) of Namibia in meeting their educational provision. A descriptive survey design was employed to collect information. The sample comprised 29 teachers and 7 nomadic learners, hence the study had 36 respondents. The sampling technique was convenience and the data were collected using interviews and questionnaires as research instruments. The interview was face to face and semistructured. The collected data were presented in a narrative form and analyzed based on research questions. The study found out that challenges such as inadequate learning materials, shortage of classrooms, lack of accommodation, lack of water, insufficient food supplies and engagement of unqualified teachers in mobile schools hindered nomadic learners of Namibia in meeting their educational provision. It was revealed by respondents that schools had inadequate learning facilities. It was also shown that the schools used tent classrooms and under tree classes. Participants revealed that schools did not have water sources of their own. It was also brought out that mobile schools received insufficient food that could not sustain the school term. In the light of the findings, the researcher recommended that the Namibia Ministry of Education and rightful authorities put initiatives and measures to eradicate challenges faced by the nomadic learners of Namibia in meeting their education provisions.